2010
DOI: 10.1038/ajg.2010.315
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Detection of Serrated Polyps in an Average Risk Colorectal Cancer Screening Cohort

Abstract: This study describes the detection of colorectal polyps in an average risk-screening cohort at an urban academic medical center. Detection of proximal SSAs increased during the study period. Detection of adenoma, HP, and SSA differed significantly by endoscopist. Classification of HP and SSA differed significantly by pathologist. Endoscopy and pathology practices should consider educational interventions to improve serrated polyp detection and standardize classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
316
4
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(362 citation statements)
references
References 23 publications
29
316
4
6
Order By: Relevance
“…Some studies indicate that 31% of hyperplastic polyps and 27% of nonadenomatous polyps are missed during colonoscopy (12,13), which is consistent with a high variability in serrated polyp detection among endoscopists (i.e., ranging from 8%-32% for all serrated polyps, and from 1%-18% for proximal serrated polyps; refs. 14,15). Taken together these findings highlight the need for improving detection of these lesions.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Some studies indicate that 31% of hyperplastic polyps and 27% of nonadenomatous polyps are missed during colonoscopy (12,13), which is consistent with a high variability in serrated polyp detection among endoscopists (i.e., ranging from 8%-32% for all serrated polyps, and from 1%-18% for proximal serrated polyps; refs. 14,15). Taken together these findings highlight the need for improving detection of these lesions.…”
Section: Introductionmentioning
confidence: 87%
“…It became clear that serrated polyps often have a subtle endoscopic appearance, thereby explaining the operatordependent variation in their detection, ranging from 8% to 32% (14,15). This high variability in detection highlights the need for education and training, for which a systematic approach is needed, that is, by means of videotraining, computer-aided programs, and learning from experts (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, reports that advanced imaging techniques such as narrow band imaging or chromoendoscopy can help identify and demarcate lesions may help endoscopists improve their ability to detect and completely remove these lesions ( 17,18 ). Although substantial variability in the detection rates of serrated polyps among endoscopists has been reported ( 19,20 ), Hetzel et al ( 19 ) reported that the rates increased from 2006 to 2008, indicating that recognition of these lesions can be improved.…”
mentioning
confidence: 99%